Fruithiees Food Truck / Mohd Azrul Abd Rajak ... [et al.] - Abd Rajak, Mohd Azrul; Simon, Missy; Sumbing, Azlinarichel; Majawai, Easther V.; Kee Mohd Yasin, Kee Azryn Aida (2015)
First of all, the name of our company is the Fruithiees Food Truck and the nature of our business is partnership. Our main activity is the food production and services. Our business aim is to provide peoples with fast food and beverages. The reason why we want to start toe business is because we saw toe trend of food business nowadays in overseas which is toe moving food truck business. We saw the opportunity of this business if we start it in Malaysia because tots kind of business is very new in this country. After studying this business with ail members, we decided to do toe business plan about this kind of business. We all agreed to apply toe system of moving truck business in Malaysia, and our starting point is in Kota Kinabalu Sabah. We also decided to sell fast food as our product in our very simple observation, we saw that our snack food product have high demand in market so we finally agreed to sell snack food based on fruit as our main product. Our business premise will be located at Indah Permai, Jatan Sepanggar Kota Kinabalu and toe business will operate all around toe Kota Kinabalu district. The estimated time to begin our business will be on according to our partnership agreement made on. The purpose of writing this whole business plan is to convince the venture capitalist investors, and bankers in order to raise our capital and obtain a specific amount of loan for toe beginning of our business. This business plan is to written for the guideline purpose of day-to-day management of business.